2020
DOI: 10.1002/dta.2888
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of MMB022 and identification of dihydrodiol formation in vitro using synthesized standards

Abstract: MMB022 (methyl 3-methyl-2-[1-(pent-4-en-1-yl)-1H-indole-3-carboxamido]butanoate) is a new synthetic cannabinoid with an alkene at the pentenyl side chain, a rare functional group for synthetic cannabinoids. Metabolite identification is an important step for the detection of synthetic cannabinoids in humans, since they are generally extensively metabolized. The aims of the study were to tentatively identify in vitro phase I metabolites, to confirm major metabolites using synthesized metabolites, to examine meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The presence of epoxide in the samples seems not likely but cannot be ruled out without the use of a reference standard, because the epoxidized structure is isomeric to monohydroxylated metabolites. A recently published metabolism study of MMB‐4en‐PICA (MMB‐022) by Watanabe et al has shown that a theoretical epoxide intermediate in the context of dihydrodiol biotransformation of the 4‐pentenyl tail group was not observed in pHLM incubations 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of epoxide in the samples seems not likely but cannot be ruled out without the use of a reference standard, because the epoxidized structure is isomeric to monohydroxylated metabolites. A recently published metabolism study of MMB‐4en‐PICA (MMB‐022) by Watanabe et al has shown that a theoretical epoxide intermediate in the context of dihydrodiol biotransformation of the 4‐pentenyl tail group was not observed in pHLM incubations 16 …”
Section: Resultsmentioning
confidence: 99%
“…15 The presence of epoxide in the samples seems not likely, but cannot be ruled out without the use of a reference standard, since the epoxidized structure is isomeric to monohydroxylated incubations. 16 For the unambiguous identification of a Cumyl-CBMICA uptake the metabolites M24…”
Section: Cumyl-cbmicamentioning
confidence: 99%
“…Two other relatively abundant metabolites featuring mono‐hydroxylation on the indazole ring are reported in this study, one of which is a phase 1 metabolite (B16, ranked third in abundance, as estimated by peak area) and the other a phase II glucuronidated metabolite (B5, ranked sixth in abundance, as estimated by peak area). The suggested metabolite structures are based on evaluation on LC‐QTOF‐MS data and previous studies of the biotransformation of similar SCRAs 33,34 . Comparison of retention times of the metabolites observed in the HHeps incubation samples with those obtained from the analysis of high purity synthesized reference standards under the same conditions or NMR is required for unequivocal structural confirmation.…”
Section: Resultsmentioning
confidence: 99%
“…The T A B L E 1 ADB-BUTINACA metabolites with biotransformations, chemical formulas, retention times, exact masses of the protonated molecules, mass errors from all samples, peak areas, and rankings of metabolites based on average peak area in 5 h human hepatocyte incubations and comparison with previously reported metabolites following incubation of ADB-BUTINACA with human liver microsomes 32 suggested metabolite structures are based on evaluation on LC-QTOF-MS data and previous studies of the biotransformation of similar SCRAs. 33,34 Comparison of retention times of the metabolites observed in the HHeps incubation samples with those obtained from the analysis of high purity synthesized reference standards under the same conditions or NMR is required for unequivocal structural confirmation.…”
Section: Measurement Of In Vitro Cb 1 Potencymentioning
confidence: 99%
“…134, Exclusive use of human liver microsomes has been used to study the metabolism of, MMB022, 3,5-AB-CHMFUPPYCA, ADB-FUBINACA, 5F-ADB, CUMYL-PINACA, CUMYL-4CN-B7AICA, CUMYL-4CN-BINACA, 5F-CUMYL-PINACA, AKB-48, STS-135, MAM-2201 and XLR-11 among others. 136,[164][165][166][167][168][169][170][171] The following synthetic cannabinoids have been studied using only hepatocytes, BB-22, 5C-AKB48, EG-018, PB-22, 5F-PB-22 SDB-006, AKB-48 and XLR-11 among others. [172][173][174][175][176][177][178] Several metabolism studies of synthetic cannabinoids in urine have been carried out, including of ADB-FUBINACA, AM-694, AM-2201, JWH-007, JWH-019, JWH-203, JWH-307, MAM-2201, UR-144, XLR-11, APINAC, BB-22, EG-018, EG-2201, MDMB-CHMCZCA, MDMB-FUBINACA and 5Cl-THJ-018.…”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%